Effect of Exercise and Cognitive Activity on Self-Reported Sleep Quality in Community-Dwelling Older Adults with Cognitive Complaints: A Randomized Controlled Trial - Pa, Judy (J Am Geriatr Soc, 2014)
OBJECTIVES: To compare the effects of different types of physical and mental activity on self-reported sleep quality over 12 weeks in older adults with cognitive and sleep complaints. DESIGN: Randomized controlled trial. SETTING: General community. PARTICIPANTS: Seventy-two inactive community-dwelling older adults with self-reported sleep and cognitive problems (mean age 73.3±6.1; 60% women). INTERVENTION: Random allocation to four arms using a two-by-two factorial design: aerobic+cognitive training, aerobic+educational DVD, stretching+cognitive training, and stretching+educational DVD arms (60 min/d, 3 d/wk for physical and mental activity for 12 weeks). MEASUREMENTS: Change in sleep quality using seven questions from the Sleep Disorders Questionnaire on the 2005–06 National Health and Nutrition Examination Survey (range 0–28, with higher scores reflecting worse sleep quality). Analyses used intention-to-treat methods. RESULTS: Sleep quality scores did not differ at baseline, but there was a significant difference between the study arms in change in sleep quality over time (p<.005). Mean sleep quality scores improved significantly more in the stretching+educational DVD arm (5.1 points) than in the stretching+cognitive training (1.2 points), aerobic+educational DVD (1.1 points), or aerobic+cognitive training (0.25 points) arm (all p<.05, corrected for multiple comparisons). Differences between arms were strongest for waking at night (p=.02) and taking sleep medications (p=.004). CONCLUSION: Self-reported sleep quality improved significantly more with low-intensity physical and mental activities than with moderate- or high-intensity activities in older adults with self-reported cognitive and sleep difficulties. Future longer-term studies with objective sleep measures are needed to corroborate these results.